Human Herpesvirus-6 and Roseola Infantum Meningitis - J Gordon Millichap (Pediatric Neurology Briefs, 1992)
Two infants with roseola infantum and meningitis caused by human herpesvirus-6 infection are reported from the Department of Pediatrics, College of Medicine, National Taiwan University, Taipei, Taiwan.